Less reactogenic whole-cell pertussis vaccine confers protection from Bordetella pertussis infection - Karolína Škopová; Jana Holubová; Barbora Bočková; Eva Slivenecká; João Melo Santos de Barros; Ondřej Staněk; Peter Šebo (mSphere)
ABSTRACT Pertussis resurged over the last decade in most countries that replaced the traditional whole-cell pertussis vaccines (wP) by the less reactogenic acellular pertussis vaccines (aP). The aP vaccines induce a Th2-polarized immune response and by a yet unknown mechanism hamper the clearance of Bordetella pertussis from infected nasopharyngeal mucosa. The aP-induced pertussis toxin-neutralizing antibodies effectively prevent the life-threatening pertussis pneumonia in infants, but aP-elicited immunity fails to prevent infection of nasopharyngeal mucosa and transmission of B. pertussis. In contrast, the more reactogenic traditional wP vaccines, alike natural infection, elicit a broad antibody response and trigger a Th1/Th17-polarized T cell immunity. We tackled here the reactogenicity of the conventional wP vaccines by genetic modification of the Fim2 and Fim3-producing B. pertussis strains used for wP vaccine manufacturing. Mutations were introduced into the genomes of vaccine strains (i) to reduce the TLR4 signaling potency of the lipid A of B. pertussis lipooligosaccharide (ΔlgmB), (ii) eliminate the enzymatic (immunosuppressive) activity of the pertussis toxin (PtxS1-R9K/E129G), and (iii) ablate the production of the dermonecrotic toxin (Δdnt). Experimental alum-adjuvanted wP vaccines prepared from such triply modified bacteria exhibited a reduced pyrogenicity in rabbits and a reduced systemic toxicity in mice, while conferring a comparable protection from B. pertussis infection as the unmodified wP vaccine.IMPORTANCEThe occasionally severe adverse reactions associated with some lots of the whole-cell pertussis vaccine (wP) led the industrialized nations to switch to the use of less reactogenic acellular pertussis vaccines that confer shorter-lasting protection. This yielded whooping cough resurgence and large whooping cough outbreaks are currently sweeping throughout European countries, calling for the replacement of the pertussis vaccine component of pediatric hexavaccines by an improved wP vaccine. We show that genetic detoxification of the Bordetella pertussis bacteria used for wP preparation yields a reduced reactogenicity wP vaccine that exhibits a reduced systemic toxicity in mice and reduced pyrogenicity in rabbits, while retaining high immunogenicity and protective potency in the mouse model of pneumonic infection by B. pertussis. This result has now been confirmed in a nonhuman primate model of B. pertussis infection of olive baboons, paving the way for the development of the next generation of pertussis vaccines.